HOW JOB WORK INFLUENCE ON STUDY PERFORMANCE OF (MS & PHD) STUDENTS OF SINDH: A GROUNDED THEORY APPROACH - Irfan Ali Shah; Neelam Jugwani; Zulfiqar Ali Rajper (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores how job work is influencing the study performance of students in Sindh. For this study the researcher has used grounded theory approach by Strauss & Corbin (1990), and interviews were conducted from the total 8 students who are doing job and also pursuing their higher studies simultaneously. In this study, axial coding and selective coding is being done through qualitative research software (Nvivo). The main object of the study is to observe how the job work is influencing the study performance. The results show that job work like job meetings, job timing, busy job schedule and job assignments are influencing the study performance because students are giving less time to their study and research work. Moreover, they remained absent from the classes and consequently show low academic performance. This study will help the educational institutes for developing strategies to retain their students in higher education like (MS & PhD) as well as to increase the enrollment in these study programs. This study will also help other organizations to retain their employees who want to get higher education.